LIFE SKILL EDUCATION IN BUILDING THE INDEPENDENCE OF STUDENTS AT PONDOK PESANTREN FATHUL ULUM JOMBANG - Ikfi Khoulita; Siti Khoirun Nisak; Khoirun Nisa (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
The aim of this research is to examine life skills education at Pondok Pesantren Fathul Ulum Jombang. This research is particularly interesting because, as a pesantren still using the salafiyah learning model, life skills education is an inseparable part of the curriculum. The research uses a qualitative method, with data collection through interviews, observation, and documentation. The analysis is descriptive. The results of the study show that the life skills education provided at Pondok Pesantren Fathul Ulum Jombang is fascinating due to its unique approach. Students who enter the Aliyah level are required to choose one of the available majors, one of which is the "preunur" (entrepreneurship) major. In this major, life skills education receives a larger portion than religious education, and students in this major are given the responsibility to manage the pesantren’s businesses. Another unique feature of life skills education at Pondok Pesantren Fathul Ulum Jombang is that there is a specific day dedicated to life skills education, focusing on all business aspects of the pesantren, which all students must participate in. Furthermore, the pesantren's caregivers provide lectures using the Ihya’ Ulumuddin book, specifically the chapter on work, to strengthen students' enthusiasm and belief that life skills education is just as important as religious education. The implications of life skills education at Pondok Pesantren Fathul Ulum Jombang are greatly felt by students and alumni in building their independence, both economically and in terms of entrepreneurial spirit.